HAND1, partially mediated through ape-specific LTR binding, is essential for human extra-embryonic mesenchyme derivation from iPSCs - Zukai Liu; Yuliana Tan; William F. Flynn; Lili Sun; Ponthip Pratumkaew; Juliana Alcoforado Diniz; Nelio A.J. Oliveira; Justin A. McDonough; William C. Skarnes; Paul Robson (Cell Reports)
Summary: The specification of extra-embryonic mesenchyme (ExMC) is a prime example of developmental divergence between mouse and human. Derived from definitive mesoderm during mouse gastrulation, the human ExMC first appears at peri-implantation prior to gastrulation and therefore its human cellular origin, still unknown, must differ. In a human pluripotent stem cell model, we report that ExMC shares progenitor cells with trophoblast, suggesting a trophectoderm origin. This ability to form ExMC appears to extend to human trophoblast stem cell lines. We define HAND1 as an essential regulator of ExMC specification, with null cells remaining in the trophoblast lineage. Bound by HAND1, ape-specific, endogenous retrovirus-derived LTR2B contributes to unique features of ExMC. Additionally, ExMC supports the maintenance of pluripotent stem cells, possibly reflecting a role in maintaining epiblast pluripotency through peri-implantation development. Our data emphasize the nascent evolutionary innovation in human early development and provide a cellular system to study this.